Study of anemia in geriatric population: a hospital based study in Marathwada region, Maharashtra, India - Soni, Pravin N.; Jawale, Rahul B.; Soni, Seema P. (International Journal of Advances in Medicine, 2017)
Background: In geriatric population, anemia is not only the common problem, but it may present as severe complications in this group compared with anemia in younger group. According to WHO criteria, level of hemoglobin less than 13 gm% in case of males and less than 12 gm% in females are considered as anemia.The main objective of the study was to study the various pattern of anemia in the geriatric population. Methods: The study was carried out at JIIU’s IIMSR Medical College and Noor Hospital, Badnapur, Jalna, Maharashtra, India from January 2014 to June 2015. Total number of patients taken for the study are 550 (>60 years) who attending geriatric and clinical OPD at Noor Hospital, Badnapur. Detailed haematological examination was carried out in each patient. Results: Out of 550 cases, 369 (67.09%) patients were found to be anemic. Proportions of anemia in males was 64.74% and in females 70.58%. On peripheral smear examination normocytic being the commonest and constituting 78.86%. Conclusions: Diagnosis of anemia in geriatric age group, and further to know its pattern, which thus helps in etiological diagnosis of anemia which ultimately helps in the treatment.